2019
DOI: 10.1016/j.ijid.2019.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Burden and risk factors of Shigella sonnei shigellosis among children aged 0–59 months in hyperendemic communities in Israel

Abstract: A B S T R A C TObjectives: Ultraorthodox Jewish populations living in towns with good sanitary infrastructure but with conditions of crowding have been the epicenter of Shigella sonnei shigellosis outbreaks. In this study, the incidence and risk factors of S. sonnei shigellosis in children living in an ultraorthodox community were determined. Methods: Data for the years 2000-2013 for all reported culture-proven S. sonnei shigellosis cases in children aged 0-59 months in the city of Elad were compared with data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Studies of ultraorthodox Jewish communities in Israel and abroad (34) have shown that in regions of endemicity the incidence of S. sonnei shigellosis follows a cyclical pattern, with epidemics occurring every 2 years. The timing of these cyclical epidemics of S. sonnei shigellosis are attributed to the waning rate of natural immunity to the organism (33,34). It is likely that a similar phenomenon occurs among GBMSM; natural exposure to Shigella species through intensive shigellosis epidemics in the GBMSM community may also increase immunity levels in individuals belonging to sexual networks.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of ultraorthodox Jewish communities in Israel and abroad (34) have shown that in regions of endemicity the incidence of S. sonnei shigellosis follows a cyclical pattern, with epidemics occurring every 2 years. The timing of these cyclical epidemics of S. sonnei shigellosis are attributed to the waning rate of natural immunity to the organism (33,34). It is likely that a similar phenomenon occurs among GBMSM; natural exposure to Shigella species through intensive shigellosis epidemics in the GBMSM community may also increase immunity levels in individuals belonging to sexual networks.…”
Section: Discussionmentioning
confidence: 99%
“…The low inoculum required to cause shigellosis (100-1000 organisms) 22 facilitates transmission of the disease, and explains the frequent failure of adequate sanitary and hygienic measures to prevent shigellosis, 12 even in high-income countries. 19,23 Therefore, the development of an efficacious Shigella vaccine is highly desirable and particularly needed for young children residing in LMICs and other regions with high disease burden.…”
Section: Introductionmentioning
confidence: 99%
“…The timing of these cyclical epidemics of S. sonnei shigellosis are attributed to the waning rate of natural immunity to the organism [30,31]. It is likely that a similar phenomenon occurs among GBMSM; natural exposure to Shigella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of ultraorthodox Jewish communities in Israel and abroad [31] have shown that in endemic regions the incidence of S. sonnei shigellosis follows a cyclic pattern with epidemics every 2 years.…”
Section: Discussionmentioning
confidence: 99%